Evaluation of portable devices for medicine quality screening: Lessons learnt, recommendations for implementation, and future priorities - Caillet, C; Vickers, S; Vidhamaly, V; Boutsamay, K; Boupha, P; Zambrzycki, S; Luangasanatip, N; Lubell, Y; Fernández, FM; Newton, PN (Public Library of Science, 2021)
Céline Caillet and co-authors discuss a Collection on use of portable devices for the evaluation of medicine quality and legitimacy.